PENGARUH MEDIA SOSIAL DAN E COMMERCE TERHADAP KEPUTUSAN PEMBELIAN PADA INDOMARET DI KABUPATEN TANA TORAJA - devi, olivia (Jurnal Metaverse ADPERTISI, 2023)
The purpose of this study is to find out how social media, e-commerce, and Indomaret purchase decisions are made. As well as to find out how much influence social media has on purchasing decisions, the influence of e-commerce on purchasing decisions and the influence of social media and e-commerce on purchasing decisions. In this study, the independent variable (X) is social media and e-commerce, while the dependent variable (Y) is the purchase decision. This research is a sample research in which consumers are the respondents in the research, for data collection using a questionnaire with a total of 36 respondents. The analytical method used is quantitative research using the case study method. To process data, the author uses the help of Microsoft Excel 2013 and SPSS 29 For Windows programs. The results of the study stated that social media was in the good category, e-commerce was in the good category, purchasing decisions were in the good category.